Council Highlights: Minutes of the 540th Meeting of the Council, 13 January 1968 (1968)
This summary is published so that CMA membership may be advised in brief of the actions of the Association's Council. It covers only major actions and is not intended as a detailed report. Full minutes of these meetings are available upon any member's request to the CMA Headquarters office or your component society.